2008
DOI: 10.4049/jimmunol.180.1.281
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complex-Bearing Follicular Dendritic Cells Deliver a Late Antigenic Signal That Promotes Somatic Hypermutation

Abstract: We reasoned that immune complex (IC)-bearing follicular dendritic cells (FDCs) promote somatic hypermutation (SHM). This hypothesis was tested in murine germinal center reactions induced in vitro by coculturing 6-day (4-hydroxy-3-nitrophenyl) acetyl-primed but unmutated λ+ B cells, chicken γ-globulin (CGG) memory T cells, FDCs, and ICs (anti-CGG plus NP-CGG). Mutations in primed λ+ B cells were obtained only when both FDCs and immunogen were present. FDCs alone promoted B cell survival and Ab production but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
47
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 54 publications
3
47
0
Order By: Relevance
“…FDCs are critical for the induction of a complete humoral immune response, because these cells are required to capture IC-bound Ags and stimulate cognate B cells (9,10), leading to an increase of the Ag-specific memory B cell population and expansion of the Ab-secreting plasma cells (13)(14)(15). FDCs have also been shown to function as a reservoir of Ag for uptake by lymphonodal DCs (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FDCs are critical for the induction of a complete humoral immune response, because these cells are required to capture IC-bound Ags and stimulate cognate B cells (9,10), leading to an increase of the Ag-specific memory B cell population and expansion of the Ab-secreting plasma cells (13)(14)(15). FDCs have also been shown to function as a reservoir of Ag for uptake by lymphonodal DCs (16).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that cognate B cells acquire a portion of the FDC membrane together with the Ag (9). B cell activation determines both the expansion of the Ag-specific memory B cell compartment and the formation of plasma cells (13)(14)(15). Thus, FDCs exert a primary role in the induction of a humoral immune response.…”
mentioning
confidence: 99%
“…Ab persistence is mediated by long-lived plasma cells in the bone marrow (BM) and generation of Ab-secreting cells (AbSCs) from memory B cells (7). High-affinity memory B cells are selected in germinal centers (GCs) in lymphoid organs (8), mediated by follicular dendritic cells (FDCs) retaining immune complexes (ICs) through FcRs and complement receptors (9). Cells involved in the initial deposition of ICs on FDCs include marginal metallophilic macrophages (MMMs) in spleen and subcapsular sinus macrophages of lymph nodes that both express CD169/MOMA-1 (10,11).…”
mentioning
confidence: 99%
“…The nonmobile FDCs remain in the GCs where their intertwining dendrites create extensive Ag retaining reticula (ARR) intimately in contact with numerous mobile B cells (5,6). In GCs, which are typically involved in refining humoral immunity to TD Ags, FDCs promote: B cell survival, Ig class switching, somatic hypermutation, selection of somatically mutated B cells with high-affinity receptors, affinity maturation, B memory production, and induction of secondary IgG and IgE responses (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%